Pengaruh Program Pembelajaran Kewirausahaan Terhadap Minat Pendirian Startup Jasa Teknis di Kalangan Teknisi Bandara - Feti Fatonah; Priyohutomo Agung S; Rifki Baihaki; Irhas Adriyono; Hanzalah Gustan N; Fernanda Harpa F (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to analyze and test the influence of entrepreneurship learning programs on the increase in interest in establishing technical service startups among airport technicians. The aviation sector requires continuous innovation, and technicians, with their profound technical expertise, possess significant potential to become entrepreneurs (technopreneurs). However, they often lack business orientation. Materials and methods. The research method used is quantitative with a survey approach, involving a random sample of airport technicians who have participated in entrepreneurship learning programs (such as business training, startup ideology workshops, and feasibility studies). Data were collected through structured questionnaires and analyzed using simple linear regression. Results. The results show a positive and significant influence of the entrepreneurship learning program variable on the interest in establishing technical service startups. Effective learning, particularly that which emphasizes market opportunity identification, risk management, and business model formulation, significantly increases the self-confidence and intention of technicians to transition from technical employees to owners of aviation technical service businesses (such as independent Maintenance, Repair, and Overhaul services, or drone-based airport technology solutions). Conclusions. These findings recommend the necessity of a more comprehensive integration of practical entrepreneurship material into vocational education curricula and professional development programs for airport technicians.